PENERAPAN KONSTRUKSI HIJAU PADA PROYEK APARTEMEN X DI JAKARTA PUSAT - Narisa Adistianti; I Ketut Sucita (Construction and Material Journal, 2020)
Along with the Jakarta Governor rules no. 38/2012 about green building, The Contractors in the capital has been practicing to implement green construction in building construction. This is done by a contractor state-owned or private contractor. The purpose of this research is analyzing the application of green construction by state owned contractors who is not a member of green building council Indonesia. Collecting data which used in this research was questionnaire, observation, and documentation. The reference of indicators are from regulations, rating tools GBCI and models assessment green construction developed by Wulfram Ervianto. The Indicators are health program and occupational safety, environmental health work, air quality construction phase, election and operational construction phase, planning and scheduling construction equipment, documentation construction project, building & enviroment management, training for subcontractor, waste management, the source and cycle construction, material storage and protection, appropriate site development, reduction ecological footprint the project, protection plan, water conservation, and efficiency & energy conservation. The method of analysis data questionnare are descriptive analysis. The result of research is average value of the implementation of green construction by 85,08 % which means that green construction points of the indicators as a whole has taken and implemented by contractor. Keywords: Green Construction, Construction Phase, GBCI.